Pembelajaran Blended Learning Melalui Google Classroom - Edy Sabara; Sabran Sabran (Seminar Nasional LP2M UNM, 2019)
Access to extensive learning resources for students gives the room for lecturers to move from lecturer centered learning to student centered learning. This can be implemented in learning based on blended learning using the google classroom application that integrates online learning outside the classroom and face to face in the classroom. With the internet that provides various learning management systems such as Google Classroom, teachers can create virtual classes to carry out online learning outside the classroom so that students are accustomed to learning actively and independently in learning. This study aims to describe the learning process of blended learning, assess student learning outcomes, find out the differences in learning outcomes of male and female students, and assess student responses. This research uses descriptive method to take the subject of material science subjects in the vocational education program of FT-UNM mechatronics, which amounted to 36 students. Data collection techniques in the form of observation, tests, and questionnaires. Data analysis techniques in the form of descriptive and inferential statistics. The results showed the learning process was in the very good category, student learning outcomes were in the moderate category, there were differences in learning outcomes between male and female students, and student responses were in the very high category.